Viral Infections and Cutaneous Drug-Related Eruptions - Anci, Eleonora; Braun, Camille; Marinosci, Annalisa; Rodieux, Frédérique; Midun, Elise; Torres, Maria-Jose; Caubet, Jean-Christoph (Frontiers in Pharmacology, 2021)
In the general population, up to 10% of children treated by antibiotics have cutaneous adverse drug reaction, but allergy is confirmed in less than 20% of patients. Most of the non-allergic reactions are probably due to virus, such as enterovirus acute infection or Ebstein-Barr Virus (EBV) acute infection or reactivation. Especially in children, viruses have the propensity to induce skin lesions (maculopapular rash, urticaria) due to their skin infiltration or immunologic response. In drug-related skin eruptions, a virus can participate, inducing an immune predisposition to react. The culprit antibiotic is then the trigger for reacting. Even in severe drug-induced reactions, such as Drug Reaction with Eosinophilia and Systemic Symptoms (DRESS) syndrome, viruses take part in immune phenomena, especially herpes viruses. Understanding the mechanisms of both virus and drug -induced skin reaction is important to develop our clinical reflection and give an adaptive care to the patient.